2018
DOI: 10.1038/s41598-018-21565-w
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus addition changes belowground biomass and C:N:P stoichiometry of two desert steppe plants under simulated N deposition

Abstract: Many studies have reported that increasing atmospheric nitrogen (N) deposition broadens N:phosphorus (P) in both soils and plant leaves and potentially intensifies P limitation for plants. However, few studies have tested whether P addition alleviates N-induced P limitation for plant belowground growth. It is also less known how changed N:P in soils and leaves affect plant belowground stoichiometry, which is significant for maintaining key belowground ecological processes. We conducted a multi-level N:P supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
6
17
1
Order By: Relevance
“…According to a generalization proposed by Tessier and Raynal [54], the plant growth rate can be reflected by the N:P ratio and P limitation often arises when the leaf N:P ratio surpasses 16. Although plant roots are considered less sensitive to environmental changes than leaves, some studies have demonstrated that belowground stoichiometry is also sensitive to environmental changes [22]. In our research, N treatment significantly improved the root N:P ratio to >16 (Fig.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Authsupporting
confidence: 52%
See 2 more Smart Citations
“…According to a generalization proposed by Tessier and Raynal [54], the plant growth rate can be reflected by the N:P ratio and P limitation often arises when the leaf N:P ratio surpasses 16. Although plant roots are considered less sensitive to environmental changes than leaves, some studies have demonstrated that belowground stoichiometry is also sensitive to environmental changes [22]. In our research, N treatment significantly improved the root N:P ratio to >16 (Fig.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Authsupporting
confidence: 52%
“…These results demonstrate that P application (40 mg kg −1 ) significantly increases plant tissue (leaves, branches, stems, and roots) P concentrations but decreases leaf, branch, and root N:P ratios, which supports our first hypothesis that P addition can significantly increase plant P concentration but decrease the N:P ratio of Chinese fir seedlings. Huang et al [22] reported that P addition significantly increases plant P concentrations but significantly decreases the root N:P ratio of licorice (Glycyrrhiza uralensis) and Pennisetum (Pennisetum alopecuroides). This might be explained by the fact that plants can take up more P in this context, leading to increased plant P concentrations.…”
Section: Effect Of P Addition On Biomass Production and N:p Stoichiommentioning
confidence: 99%
See 1 more Smart Citation
“…Stoichiometric nutrient ratios were used to infer changes in the relative availability of N and P, assessing the likelihood of a shift in the limiting nutrient from N to P [6,56]. Previous research indicated that increasing the N deposition can promote plant growth by improving the soil N supply, whereas increasing the P addition can stimulate the growth of plants limited by P deficiency [57]. We observed that different N and P addition treatments, along with seasonal changes, had measurable effects on the C:N:P stoichiometry in Chinese fir, which was reported in other species [58].…”
Section: Seasonal Response Of Ecological Stoichiometry Under N and P mentioning
confidence: 99%
“…2018). Importantly, this work suggests that community ecological stoichiometry can be important for plant species diversity (Huang J et al . 2018).…”
Section: Introductionmentioning
confidence: 99%